An explanation of the profitability and market power of marginalized microenterprises - Ramirez, Natanael; Mungaray, Alejandro; Aguilar, Jose G; Inzunza, Ramon (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
This paper analyzes the behavior of marginalized microenterprises under an imperfect competition framework, where said economic units are capable of fixing a price above their marginal costs which allows them to survive and even be profitable despite their typical operating conditions. To prove this, we use an econometric model that considers the Lerner index as a variable dependent on a set of qualitative variables previously classified in accordance to their area of influence. We conclude that these microenterprises are capable of being profitable and operate with market power through their advertising and sales strategies and the flexibility in their productive process. In any case the pricing power is highly influenced by the socioeconomic conditions of the market in which it operates.